Successor selection in times of continuity and renewal - A discrete choice-experiment - Sebastian Hillebrand; Thorsten Teichert (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
Succession in family firms generates unique and critical challenges for these organizations. Owing to family firms' idiosyncratic organizational context, family firm scholars suggest that insider successors should be preferred to outsider successors. However, recent strategic management and entrepreneurship research indicates that the suitability of an insider or outsider successor depends strongly on the firm's specific strategic context. We build on a discrete-choice- experiment with 123 decision-makers to test if the strategic context affects the successor selection in family firms. The results reveal that the demand for an insider candidate (instead of an outsider candidate) is significantly lower if a family firm aims at renewal rather than continuity. Yet, in contrast to strategic management research, the findings imply that the idiosyncrasies of a family firm prevail even if the business faces substantial renewal.
Keywords: 650; family firm; innovation; succession; successor selection; insiderness; outsiderness